Prevention literacy: community‐based advocacy for access and ownership of the HIV prevention toolkit. Issue 1 (30th September 2016) - Parker, Richard G; Perez‐Brumer, Amaya; Garcia, Jonathan; Gavigan, Kelly; Ramirez, Ana; Milnor, Jack; Terto, Veriano
Abstract : Introduction: Critical technological advances have yielded a toolkit of HIV prevention strategies. This literature review sought to provide contextual and historical reflection needed to bridge the conceptual gap between clinical efficacy and community effectiveness (i.e. knowledge and usage) of existing HIV prevention options, especially in resource‐poor settings. Methods: Between January 2015 and October 2015, we reviewed scholarly and grey literatures to define treatment literacy and health literacy and assess the current need for literacy related to HIV prevention. The review included searches in electronic databases including MEDLINE, PsycINFO, PubMed, and Google Scholar. Permutations of the following search terms were used: "treatment literacy, " "treatment education, " "health literacy, " and "prevention literacy." Through an iterative process of analyses and searches, titles and/or abstracts and reference lists of retrieved articles were reviewed for additional articles, and historical content analyses of grey literature and websites were additionally conducted. Results and discussion: Treatment literacy was a well‐established concept developed in the global South, which was later partially adopted by international agencies such as the World Health Organization. Treatment literacy emerged as more effective antiretroviral therapies became available. Developed from popular pedagogy and grassroots efforts during an intense struggle for treatment access, treatment literacy addressed the need to extend access to underserved communities and low‐income settings that might otherwise be excluded from access. In contrast, prevention literacy is absent in the recent surge of new biomedical prevention strategies; prevention literacy was scarcely referenced and undertheorized in the available literature. Prevention efforts today include multimodal techniques, which jointly comprise a toolkit of biomedical, behavioural, and structural/environmental approaches. However, linkages to community advocacy and mobilization efforts are limited and unsustainable. Success of prevention efforts depends on equity of access, community‐based ownership, and multilevel support structures to enable usage and sustainability. Conclusions: For existing HIV prevention efforts to be effective in "real‐world" settings, with limited resources, reflection on historical lessons and contextual realities (i.e. policies, financial constraints, and biomedical patents) indicated the need to extend principles developed for treatment access and treatment literacy, to support prevention literacy and prevention access as an integral part of the global response to HIV.